ANALYSIS OF ATOPIC DERMATITIS AND ECZEMA RESISTANT FORMS ASSOCIATION WITH THE EXPRESSION OF XENOBIOTIC BIOTRANSFORMATION GENES IN THE SKIN OF PATIENTS - Milkoto , N.; Pankratov , O.; Poluyan , O.; Shimanskaya , I.; Rudenkova, T.; Kostiuk , S.; Pankratov , O. (EurasianUnionScientists, 2020)
As a result of the studies, a reliable association of the course of atopic dermatitis and eczema (resistant, often long-term relapsing, continuously-relapsing) with an increase in the expression levels of xenobiotic biotransformation genes (UGT1A7, HMOX2, BLVRA, CCL13, APOBR, ABCC2, GSTP1) in the skin was determined. The data obtained during the studies allow us to recommend the use of a method for assessing the expression levels of xenobiotic biotransformation genes in skin scrapings, based on real-time PCR, for early diagnosis and an objective choice of treatment tactics in patients suffering from resistant, often long-term, continuously-relapsing forms of atopic dermatitis and eczema.